(untitled) (Global Journal of Medical Research, 2019)
Neurogenic tumors are rare in the oral cavity. Neurofibroma is a rare benign nonodontogenic tumor which may present either as a solitary lesion or as part of the generalized syndrome of neurofibromatosis or von Recklinghausen’s disease (VRD) of the skin. The rarity of benign lingual tumors and their distinctive histopathological features have prompted us to report this case.